2020
DOI: 10.1111/hex.13025
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of mental health service user and carer perspectives on safety issues in UK mental health services

Abstract: BackgroundService user and carer perspectives on safety issues in mental health services are not well known and may be important in preventing and reducing harm. The development of the Yorkshire Contributory Factors Framework—Mental Health (YCFF‐MH) provides a broad structure within which to explore these perspectives.ObjectiveTo explore what service users of mental health services and their carers consider to be safety issues.Design, setting and participantsQualitative interviews with 13 service users and 7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…They described the approach to safety in the community as focused less on the medical model. This reflects previous findings on patient's perceptions of safety in the community (Berzins et al 2020). Although, Coffey et al (2017) found that risk assessment and care planning in the community is conservative, and patients are often not involved.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…They described the approach to safety in the community as focused less on the medical model. This reflects previous findings on patient's perceptions of safety in the community (Berzins et al 2020). Although, Coffey et al (2017) found that risk assessment and care planning in the community is conservative, and patients are often not involved.…”
Section: Discussionsupporting
confidence: 85%
“…This reflects previous findings on patient’s perceptions of safety in the community (Berzins et al . 2020). Although, Coffey et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations